THE EFFECT OF WARM COMPRESSES AND EFFLEURAGE MASSAGE ON LOWER BACK PAIN IN PREGNANT WOMEN IN THE THIRD MONTH OF PREGNANCY IN THE DONOMULYO COMMUNITY HEALTH CENTER WORK AREA - Aprilia Suci Hatitama; Widia Shofa Ilmiah (Journal of Public Health Science, 2026)
Lower back pain is one of the most common discomforts experienced by pregnant women during the third trimester due to physiological and postural changes during pregnancy. Safe and effective non-pharmacological interventions are needed to help reduce pain. This study aimed to analyze the effect of warm compresses and effleurage massage on lower back pain among third-trimester pregnant women in the Donomulyo Community Health Center area Methods: A pre-experimental study with a one-group pretest–posttest design was conducted involving 20 third-trimester pregnant women selected through purposive sampling. Pain intensity was measured before and after the intervention using the Numeric Rating Scale (NRS). Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of 0.05.  Before the intervention, most respondents experienced moderate to severe lower back pain. After receiving warm compresses and effleurage massage, pain intensity decreased, with most respondents reporting mild pain or no pain. Statistical analysis showed a p-value of <0.05, indicating a significant reduction in pain following the intervention. Warm compresses and effleurage massage were effective in reducing lower back pain among third-trimester pregnant women. These interventions can be considered safe, simple, and non-pharmacological alternatives for pain management during pregnancy.